Differences In Learning Interest Between Male And Female Students On Cullinary Skills Competencies At Smk N 6 Padang - Vinari, Chelyani; Elida, Elida (Universitas Negeri Padang, 2023)
This research was motivated by differences in the learning interests of male and female students in the Culinary Skills Competency at SMK N 6 Padang as evidenced by the average score of female students being higher than male students. This study aims to describe: 1) The learning interest of male students in the Culinary Skills Competency at SMK N 6 Padang, 2) The learning interest of female students in the Culinary Skills Competence at SMK N 6 Padang, 3) Differences in the learning interests of male and female students Girls at SMK N 6 Padang. This type of research is descriptive comparative. The population in this study were male and female students in the Culinary Skills Competency at SMK N 6 Padang, totaling 296 students. The sampling technique used the Proportional Random Sampling technique with a total of 84 students consisting of 42 male students and 42 female students. The data collection technique uses a questionnaire (questionnaire) through the google form using a Likert Scale that has been tested for validity and reliability. The results showed that the learning interest of male students in the culinary skills competency nat SMK N 6 Padang was high, while the learning interest of female students in the culinary skills competency at SMK N 6 Padang was very high. The average value of male students' learning interest has an average of 187.43 and female students have an average of 193.12. Based on these results it was concluded that the learning interest of female students was higher than that of male students.